The imperial rulership and childhood studies in Late Antiquity: the child-emperor patterns in the Late Roman West - Silva, Érica Cristhyane Morais da (Romanitas - Revista de Estudos Grecolatinos, 2014)
Review of: McEVOY, M. A. Child emperor rule in the late roman west (a.D. 367‑455). Oxford: Oxford University, 2013. 384 p.